Monetary Conditions Index in Singapore. - Poon, Wai Ching; Habibullah, Muzafar Shah; Baharumshah, Ahmad Zubaidi; Mohamed, Azali (ICFAI University Press, 2008)

(untitled)
This paper looks at bound test approach for cointegration analysis, to verify the stability of Singaporean real Gross Domestic Product (GDP), to construct the Monetary Conditions Index (MCI) over the quarterly period 1981:1-2004:4. The bounds test confirms a long-run equilibrium relationship between the output and its determinants, namely short-term and long-term interest rate, exchange rate, claims on private sector, and share prices. Results reveal evidence of cointegration between these variables in both short and long run. As such, this has further verified the stability of the Singaporean output demand function to construct the Monetary Conditions Index (MCI), and how the Monetary Authority of Singapore (MAS) responds to exchange rate changes and whether the policy responses differ. The study has evidently showed that the actual monetary stance reacts corresponding to the MCIs.